Health benefits of Moringa oleifera: Used as an anti-diabetic agent - Amir Hamza, Mostafa; Naimuzzaman, Mollah; Roy, Swapan Kumar (International Journal of Agricultural Research, Innovation and Technology, 2023)
The medicinal plant, Moringa oleifera is frequently used in conventional healthcare to treat various conditions, including diabetes. The scientific evidence regarding M. oleifera's anti-diabetic characteristics and its potential as a supplemental treatment for diabetes control are examined in this review study. Studies have shown that M. oleifera has potent anti-diabetic properties, lowering blood sugar levels, enhancing insulin sensitivity, and decreasing complications from the disease. These benefits are thought to be caused by the plant's bioactive chemicals, such as flavonoids and polyphenols, which boost insulin secretion, prevent intestinal glucose absorption, and lessen oxidative stress. It has also been demonstrated that M. oleifera positively affects lipid metabolism, reducing overall cholesterol, triglycerides, and LDL cholesterol levels while raising HDL cholesterol levels. Additionally, it has been demonstrated that the plant possesses anti-inflammatory and antioxidant qualities that may strengthen its anti-diabetic benefits by lowering inflammation and oxidative stress, which are connected to the onset and progression of diabetes. People with diabetes may benefit from the potential anti-diabetic qualities of M. oleifera. Additional study is required to ascertain the ideal dose, duration, and safety of employing M. oleifera as an anti-diabetic medication. As a result, M. oleifera needs to be utilized as supplemental therapy under the guidance of a medical expert. Int. J. Agril. Res. Innov. Tech. 13(1): 96-102, June 2023